Massive heterotopic ossification in Guillain-Barré Syndrome : a rare case report. - Ohnmar H.,; Syed Waseem Ahmad, Sharifah Roohi; Naicker, A. S. (Societa Editrice Universo, 2010)
Heterotopic ossification (HO) is the abnormal development of bone within soft tissue and a rare complication in Guillain-Barré syndrome (GBS). Only a few cases had been reported so far. We present the case of a 39-year-old man who had been diagnosed to have GBS about 10 years ago, presenting with severe limitation of both active and passive range of motion in bilateral shoulder, elbow and hip joints and was found to have massive heterotopic ossification. In our patient, it could be a myriad of factors such as prolonged ICU stay with mechanical ventilation and hypoxia, long-standing immobilization and hypomobility with incomplete flaccid paralysis.